The Effect of Peer-Banks on Bank Liquidity Management: The Case of Islamic Banks in Indonesia - Warninda, Titi Dewi; Aisy, Diamantin Rohadatul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
This study aims to analyze the influence of peer banks on the liquidity management of Islamic banks in Indonesia and whether such influence is robust during the periods of the global financial crisis. This research uses fixed-effect panel data regression with robust standard error and the data of Islamic banks in Indonesia for the years 2007-2020. This research finds that peer-banks have a negative impact on Islamic bank liquidity, and it is robust in the global financial crisis periods. This study contributes to the policymakers and literature regarding the peer bank effect, especially in the liquidity management of Islamic banks. The liquidity management of Islamic banks is not only influenced by the conditions of the Islamic banks themselves but also affected by the behavior of other Islamic banks. AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh peer bank terhadap pengelolaan likuiditas bank sharia di Indonesia dan apakah pengaruh tersebut tetap ada selama periode krisis keuangan global. Penelitian ini menggunakan regresi data panel fixed-effect dengan robust standard error dan data bank sharia di Indonesia tahun 2007-2020. Penelitian ini menemukan bahwa peer-banks berdampak negatif terhadap likuiditas bank sharia, dan pengaruh tersebut tetap ada pada periode krisis keuangan global. Hasil penelitian ini memberikan kontribusi bagi pengambil kebijakan dan literatur mengenai adanya peer bank effect khususnya dalam pengelolaan likuiditas bank sharia. Pengelolaan likuiditas bank sharia tidak hanya dipengaruhi oleh kondisi bank sharia itu sendiri, tetapi juga dipengaruhi oleh perilaku bank sharia lainnya.